2013
DOI: 10.1016/j.jviscsurg.2013.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term oncological results after 400 skin-sparing mastectomies

Abstract: This study provides encouraging results suggesting that skin-sparing mastectomy is a safe and reliable option for the management of selected cases of women with invasive or in situ breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
4
7
0
Order By: Relevance
“…This is comparable to the results reported in the literature, which range from 3.5% to 19% [14,15,16]. …”
Section: Resultssupporting
confidence: 91%
“…This is comparable to the results reported in the literature, which range from 3.5% to 19% [14,15,16]. …”
Section: Resultssupporting
confidence: 91%
“…In addition to formal multi-disciplinary breast cancer care, all patients are now seen by subspecialty breast surgeons who occupy a common clinic facility with breast reconstructive surgeons. These factors, and the availability of robust data on the oncological safety of SSM and NSM in recent years, likely contributed to an increase in patients being referred for post-mastectomy reconstructions (3,(16)(17)(18). This parallels the observation that patients treated at specialized cancer centers, like those recognized by the National Cancer Institute in the USA, are reported to be 40% more likely to undergo reconstruction after mastectomy than patients treated at other institutions (19,20).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have reported no difference in oncologic outcomes between TM only and IBR following NSM/NNSM [1314151617]. Platt et al [18] reported that the oncologic outcomes of breast reconstruction did not vary in the TM only group in the Ontario Cancer Registry, which included 758 breast reconstruction and 1,516 control patients matched by age and cancer histology among the total 13,888 patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%